Ocio-Economic Determinants of Feeding Habits of University Students: A Case of Uganda Christian University Mukono District - Fhidwin Itta (Uganda Christian University, 2023)
This study was about “socio- economic determinants of feeding habits of university students in the case of Uganda Christian University Mukono District.” The objectives of the study were to find out feeding habits of university students, to Identify barriers related to the feeding habits of university students, to find out the enablers of feeding habits of university students. A case study design was used to select a sample size of 40 respondents. Purposive and simple random sampling procedures were used. Data was collected using questionnaires and interviews; it was later analyzed and presented using tables. The findings indicate that, as regards to feeding habits of university students most respondents (80%) were the students an indication that Uganda Christian University in Mukono District has intelligent students. The study further established various factors that influence the feeding habits of university students.
This is a dissertation.